AN IMPLEMENTATION OF LOAD BALANCING ALGORITHM IN CLOUD ENVIRONMENT - Kamboj, Sheenam; Ghumman, Mr. Navtej Singh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Cloud Computing is an emerging computing paradigm. It aims to share data, calculations, and service transparently over ascalable network of nodes. Since Cloud computing stores the data and disseminated resources in the open environment.So, the amount of data storage increases quickly. As we know that a cloud is the collection of many nodes, which can support various types of application that is used by the clients on a basis of pay per use. Therefore, the system, which is incurring a cost for the user should function smoothly and should have algorithms that can continue the proper system functioning even at peak usage. In this paper, a load balancing algorithm has been discussed and implemented in CloudSim environment. Multiple number of experiments have been conducted to analyze the results.